Energy bands splitting with interlayer broadening in Bi2Te3<Ni> - Gahramanov, S.Sh.; Orujova, H.V.; Badalov, A.A.; Abdullayev, N.A. (Physics and Chemistry of Solid State, 2025)
As a result of the developed technology, an ordered array of nanoislands was formed in the process of self-organization on the Bi2Te3<Ni> (0001) plane. Penetrating mainly into the interlayer space impurities create bulk periodic superstructures, and consisting of arrays of nanoislands between packet of layers, which, as a result, move apart. The symmetry of the Bi2Te3 crystal forbids the mixing of the states │s> and │dzƞ> with │px> and │py>, and │dzƞ > with the other d-states at high-symmetry points of the Brillouin zone, while mixing of all states is allowed at low-symmetry points. As a result, an increase in the potential barrier due interlayer broadening is accompanied by a shift and splitting (∆E 20 meV) of some bands and the formation of an energy gap.